👤

Dacă (x - 2)³ - 9x + 18 = (x + a)(x + b)(x + c), atunci a+b+c=-​

Răspuns :

(x - 2)³ - 9x + 18 =

= (x - 2)² - 9(x - 2)

= (x - 2)·[(x - 2)² - 3²]

= (x - 2)·(x - 2 - 3)·(x - 2 + 3)

= (x - 2)·(x - 5)·(x + 1)

[tex](x - 2)(x - 5)(x + 1) = (x + a)(x + b)(x + c)\\[/tex]

x - 2 = x + (-2) = x + a ⇒ a = -2

x - 5 = x + (-5) = x + b ⇒ b = -5

x + 1 = x + c ⇒ c = 1

[tex]a+b+c=(-2)+(-5)+1 = -7+1 = \bf -6[/tex]

Răspuns:

  • a + b + c = - 6

Explicație pas cu pas:

(x - 2)³ - 9x + 18 = (x + a)(x + b)(x + c)

(x - 2)³ - 9(x - 2) = (x + a)(x + b)(x + c)

(x - 2)([x - 2)² - 9]) = (x + a)(x + b)(x + c)

(x - 2)((x - 2 - 3)(x - 2 + 3) = (x + a)(x + b)(x + c)

(x - 2)(x - 5)(x + 1) = (x + a)(x + b)(x + c)

a = - 2

b = - 5

c = 1

a + b + c = - 2 + (-5) + 1 = - 2 - 5 + 1 = - 7 + 1 = - 6